LITERATURE REVIEW: KEPATUHAN TERAPI DIET GLUTEN FREE CASEIN FREE TERHADAP PERILAKU ANAK AUTIS - Astuti, Wahyu Tri; Hariyani, Christina Agatha; Alviana, Fifi (Jurnal Ilmiah Kesehatan, 2021)
Purpose: Autistic behavior arises due to disturbances in the digestive process of peptides in autistic children causing aggressive behavior, giving a peptide-free diet containing casein and gluten is an effort to reduce autistic behavior so that parental compliance is required to provide a GFCF-free diet. This study aims to analyze the effectiveness of gluten and casein-free diet adherence to reduce the behavior of autistic children. Methods: This study was a cross sectional study with a literature study approach on the results of previous studies that discuss the adherence to GFCF diet therapy on the behavior of autistic children. The research sample was taken by random sampling as many as 3 journals that met the inclusion and exclusion criteria. Results: Effective adherence to GFCF diet therapy was given to autistic children with the characteristics of parents who have autistic children aged 2-11 years, high school/college education and work. Conclusion: Compliance with GFCF diet therapy can effectively reduce the behavior of autistic children.